Integrated On-Chip Microfluidic Immunoassay for Rapid Biomarker Detection. (2016) - Garg, N.; Vallejo, D.; Boyle, D.; Nanayakkara, I.; Teng, A.; Pablo, J.; Liang, X.; Camerini, D.; Lee, A.P.; Felgner, P.
Abstract: Infectious diseases remain a major health concern in many parts of the developing world, where access to adequate health care and modern diagnostic tools are absent. Current diagnostic technologies like ELISA and PCR require large sample volumes, bulky, expensive instrumentation, highly trained personnel, long experimental time, and a modern infrastructure that developing countries lack. Hence, portable, low cost tools would be a huge first step towards making accurate diagnostics available to a wider range of patients worldwide. In this work, we present a portable, microfluidic platform, controlled via a smartphone application, that requires no external pumping and is capable of rapid (within 18 minutes) 6-step colorimetric detection of an array of vaccinia virus proteins spotted on a nitrocellulose pad. We envision this platform as a first step to a fully integrated, portable immunoassay that can be used to expand global healthcare.